Comparing consumer perceptions of appliances' electricity use to appliances' actual direct-metered consumption. (21st October 2019) - Lesic, Vedran; Glasgo, Brock; Krishnamurti, Tamar; Bruine de Bruin, Wändi; Davis, Matthew; Azevedo, Inês Lima
Abstract: Many strategies for reducing residential energy consumption—including product labelling programs, subsidies for the purchase of efficient devices, behavioral programs that encourage efficient energy use, and others—rely on building owners and end users to make informed investment and operational decisions. These strategies may be ineffective if consumers are unaware of how much electricity is used by different devices in their homes and buildings. This study therefore compares consumers' perceptions of their appliances' electricity use to these appliances' actual direct-metered electricity consumption. Using an online survey, 118 homeowners from Austin, Texas were asked to estimate the energy consumption of six household devices which were monitored in the participants' homes. Homeowners were randomly assigned to assess their appliance-specific electricity use in terms of energy units (kWh/month) or energy cost units (/month) for an average summer month. Consistent with previous studies, participants overestimated the energy consumed by their low energy consuming devices and slightly underestimated that of their most energy-consuming device. Results also showed that responses of the experimental groups estimating their consumption in energy units and energy cost units were similar, the accuracy of the two groups' perceptions was similar, and levels of confidence in the two groups were similar. These results suggest that targeted information campaigns focused on air conditioning energy consumption and device power reduction opportunities could improve consumer decision-making to save energy and reduce demand.